1984
DOI: 10.1126/science.6505691
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Mechanisms of Pain Inhibition: Activation by Stress

Abstract: Portions of the brain stem seem normally to inhibit pain. In man and laboratory animals these brain areas and pathways from them to spinal sensory circuits can be activated by focal stimulation. Endogenous opioids appear to be implicated although separate nonopioid mechanisms are also evident. Stress seems to be a natural stimulus triggering pain suppression. Properties of electric footshock have been shown to determine the opioid or nonopioid basis of stress-induced analgesia. Two different opioid systems can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
287
1
18

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 522 publications
(319 citation statements)
references
References 92 publications
13
287
1
18
Order By: Relevance
“…While the significant improvement in WB at the equivalent high-dose pregabalin indicated that it provided a successful analgesic effect, the potential sedative side effects observed at this dose in the OF and burrowing assays suggest that this result was confounded and may represent a false positive resulting from the sedative effects of the drug. In contrast to the WB assay, the burrowing assay may not result in potential false positives/negatives induced by restraining the animal (Terman et al, 1984;Imbe et al, 2006;Mogil, 2009). The burrowing assay could, therefore, be used to discriminate between analgesic doses that impair movement, which according to previous reports, the WB assay cannot (Andrews et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the significant improvement in WB at the equivalent high-dose pregabalin indicated that it provided a successful analgesic effect, the potential sedative side effects observed at this dose in the OF and burrowing assays suggest that this result was confounded and may represent a false positive resulting from the sedative effects of the drug. In contrast to the WB assay, the burrowing assay may not result in potential false positives/negatives induced by restraining the animal (Terman et al, 1984;Imbe et al, 2006;Mogil, 2009). The burrowing assay could, therefore, be used to discriminate between analgesic doses that impair movement, which according to previous reports, the WB assay cannot (Andrews et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As the animal is restrained, data from the WB assay do not distinguish between doses of sedatives that might impair movement and motor function. It has also been suggested that assays that restrain animals could elicit a stress response (Mogil, 2009), leading to increased pain tolerance due to stress-induced analgesia (Terman et al, 1984) or increased sensitivity to pain due to stress-induced hyperalgesia (Imbe et al, 2006). Stress-induced analgesia/hyperalgesia could, therefore, lead to false positives/negatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They, and others, have reported that descending inhibitory systems are suppressed by barbiturates (Frank and Ohta 1971;Collins et al 1990). Since these reports, others showed that pentobarbital blocks shock-induced analgesia (Terman et al 1984;Grau 1987) and other forms of anesthesia were shown to diminish the inhibition of dorsal horn neuron firing seen after noxious stimulation (Tomlinson et al 1983). The exact mechanism through which this occurs remains unknown, although the inhibitory neurotransmitter GABA appears to play a major role (Asana and Ogasawara 1981;Olsen and Snowman 1982;Sivam et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory signal, is believed to originate in the periaqueductal gray, travel to the rostroventral medulla, including the nucleus raphe magnus (NRM), and then to the spinal cord through serotonergic fibers that descend through the DLF to suppress firing of neurons within the dorsal horns (Mayer et al 1971;Oliveras et al 1974;Fields 1979, 1984). This antinociceptive system can be engaged by aversive environmental stimuli, such as shock and restraint (Madden et al 1977;Terman et al 1984;Tricklebank and Curzon 1984). In the case of shock and other localized noxious stimuli, the antinociception is correlated with the inhibition of nociceptive neurons within the spinal cord and occurs in areas distant from the stimulation site (Morgan and Whitney 1996).…”
Section: Introductionmentioning
confidence: 99%